Implementación del sistema de gestión de la seguridad y salud en el trabajo según el decreto 1072 de 2015 para la empresa CV Servicios S.A.S (2019)
This implementation begins with the diagnosis where a checklist is used which served to measure the percentage of compliance against the OSHMS that was 5% (Low), based on the diagnosis, the safety policy and objectives were updated Since the policy that had not evidenced the commitment of senior management with workers in OSH, a matrix of legal requirements is subsequently developed to identify the regulatory framework with which the company must comply, according to its nature, the matrix was developed of hazard identification, assessment and mitigation of risks in order to know what are the hazards to which workers are exposed and that workers know how to mitigate.